(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Evaluation of intervention outcomes for children with autism spectrum disorder at Quang Ninh Geriatric and Rehabilitation Hospital during 2023–2024. Subject and method: This study employed a pre-post intervention design to evaluate the outcomes of multimodal interventions on 48 children aged 24 to 72 months diagnosed with ASD, treated at the Geriatrics and Rehabilitation Hospital of Quang Ninh during 2023–2024 Results: After three months of intervention, statistically significant improvements were observed in three domains: imitation, verbal communication, and non-verbal communication (p < 0.05). At six months, five additional domains showed meaningful progress: interpersonal relationships, body movement, visual response, and overall impression of autism symptoms (p < 0.05). There were significant changes in social interaction skills (p<0.05) but no significant changes in stereotyped/repetitive behaviors (p > 0.05). Conclusion: These findings suggest that early, multimodal intervention can lead to improvements in several developmental areas for children with ASD, though certain core symptoms may require longer-term or more specialized approaches.